Building Block of Job Satisfaction in the Employees of Bank and Financial Institutions in Nepal (The Batuk, 2020)
The study aims at analyzing the determinants of job satisfaction in bank employees of Kathmandu valley, Nepal. The research has adopted analytical research design. The Exploratory Factor Analysis has been conducted to analyze the factor influencing job satisfaction of junior level bank employees in Kathmandu valley. The 31 usable sample sizes have been taken for the study purpose. The study found most significant factor as job security, years of experience, social status and financial status. The study concludes that the job security, experience and salary ad allowance are the building block of job satisfaction for junior level bank employees in Kathmandu valley.